PEMANFAATAN TEKNOLOGI AUGMENTED REALITY UNTUK MARKETING PADA UNIVERSITAS STIKUBANK SEMARANG (Jurnal Dinamika Informatika, 2014)
Increasing competition in the business world makes a lot of companies vying in creating innovative marketing strategies . Adapting technology into marketing strategy has become one of the attractive solution for businesses . One form of the use of technology in the marketing strategy is the use of Augmented Reality technology . The objective to be achieved is to make advertising interesting and innovative with the use of Augmented Reality technology in Stikubank University Semarang . This application requires a webcam ( camera ) as the input source , then the application will track and detect the marker ( marker ) . Once the marker is detected , then the object will be drawn above the building Unisbank marker as if the building was real . To create 3D objects using SketchUp and then change the format to the format supported by this application . While the manufacture of Augmented Reality using software OpenSpace3D . The results of this application is the visualization of the building Unisbank brochures displayed using Augmented Reality technology so that these applications can enhance competitiveness in marketing .   Keyword: Augmented Reality, SketchUp 3D, OpenSpace3D